Non-destructive multielement analysis of airborne particles byinstrumental neutron activation analysis - Sani, Musa -Abdullahi, Muhammad Ayuba (University of Eloued جامعة الوادي, 2022)
Durability is one of the unanswered questions limiting the wide acceptability of pozzolanic cement in the world today despite its numerous advantages. Resistance to sulfate attack is one of the durability properties of concrete. Ordinary and 10% Rice husk ash (RHA) pozzolanic cement concrete, with a mix ratio of 1:2:4 were produced. These specimens were subjected to both magnesium and sulfate attacks at 7, 28, 56 and 90 days hydration and their thermal analysis conducted. Information such as complex thermos, thermal effects (DTA) and thermogravimetric analysis (TGA) were collected in Nitrogen gas atmosphere. Hydration behaviour and state of the specimens with and without RHA were analysed. The experiment was conducted at a temperature between 30°C to 980°C and the heating speed was 10°C/min. The results of all the thermal analyses for concrete with 10%RHA (i.e the control), Na2SO4 concrete and MgSO4 were obtained and analysed. The result of the compressive strength when Ordinary Portland cement was partially substituted for RHA was also presented. The results showed RHA to be capable of enhancing the compressive strength, sulfate resistance and thermal resistance of concrete if used in the right proportion
Article
Keywords: Rice Husk Ash; Thermal Analysis; Magnesium Sulfate Attack; Sodium Sulfate attack; Hydration behaviour